2015
DOI: 10.1155/2016/2834386
|View full text |Cite
|
Sign up to set email alerts
|

Obestatin Accelerates the Healing of Acetic Acid‐Induced Colitis in Rats

Abstract: Obestatin, a 23-amino acid peptide derived from the proghrelin, has been shown to exhibit some protective and therapeutic effects in the gut. The aim of present study was to determine the effect of obestatin administration on the course of acetic acid-induced colitis in rats. Materials and Methods. Studies have been performed on male Wistar rats. Colitis was induced by a rectal enema with 3.5% acetic acid solution. Obestatin was administered intraperitoneally twice a day at a dose of 8 nmol/kg, starting 24 h a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 42 publications
5
29
0
2
Order By: Relevance
“…Previous studies in the gut have shown that reduction in cell proliferation or excessive apoptosis results in the development of ulcers [ 38 , 39 ]. On the other hand, the increase in cell renewal may cause mucosal hyperplasia, but it also leads to increased protection of the digestive system mucosa against the effects of damaging agents, as well as accelerates the reconstruction of mucosa integrity after damage [ 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in the gut have shown that reduction in cell proliferation or excessive apoptosis results in the development of ulcers [ 38 , 39 ]. On the other hand, the increase in cell renewal may cause mucosal hyperplasia, but it also leads to increased protection of the digestive system mucosa against the effects of damaging agents, as well as accelerates the reconstruction of mucosa integrity after damage [ 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have shown that obestatin affects the development and the course of colitis. Pretreatment with obestatin inhibits the development [ 47 ] and accelerates the healing [ 43 ] in acetic acid-induced colitis in rats. Similar protective and therapeutic effect of obestatin has been observed in dextran sodium sulfate (DSS)-induced colitis in rats [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…The area of colonic mucosa damage was measured using the computerized planimeter (Morphomat, Carl Zeiss, Berlin, Germany), as described previously [27,69]. …”
Section: Methodsmentioning
confidence: 99%
“…In addition to its proposed physiological actions, it appears that obestatin may also confer some benefits in GI disease. For example, in rats, obestatin protects against experimental ulcerative colitis via acute attenuation of lipid peroxidation and TH 1 ‐mediated inflammation, chronic suppression of polymorphonuclear leukocyte infiltration, induction of glutathione synthesis, improved mucosal blood flow and stimulation of cell proliferation in colonic mucosa, effects that may be mediated by activation of anti‐inflammatory cytokines (Pamukcu et al ., ; Matuszyk et al ., ). Furthermore, obestatin administration has been shown to confer protective effects against ischaemia–reperfusion injury in rat ileum (Şen et al ., ), whilst the ghrelin/obestatin ratio (but not obestatin levels) is reported to be elevated in patients with active inflammatory bowel diseases (Crohn's disease and colitis) compared with those in remission (Jung et al ., ; Alexandridis et al ., ), suggesting that obestatin signalling may play a role in this setting.…”
Section: Metabolic Actions Of Obestatinmentioning
confidence: 97%